In vivo Ebola virus infection leads to a strong innate response in circulating immune cells. (December 2016) - Caballero, Ignacio; Honko, Anna; Gire, Stephen; Winnicki, Sarah; Melé, Marta; Gerhardinger, Chiara; Lin, Aaron; Rinn, John; Sabeti, Pardis; Hensley, Lisa; Connor, John
Abstract Background Ebola virus is the causative agent of a severe syndrome in humans with a fatality rate that can approach 90 %. During infection, the host immune response is thought to become dysregulated, but the mechanisms through which this happens are not entirely understood. In this study, we analyze RNA sequencing data to determine the host response to Ebola virus infection in circulating immune cells. Results Approximately half of the 100 genes with the strongest early increases in expression were interferon-stimulated genes, such as ISG15, OAS1, IFIT2, HERC5, MX1 and DHX58. Other highly upregulated genes included cytokines CXCL11, CCL7, IL2RA, IL2R1, IL15RA, and CSF2RB, which have not been previously reported to change during Ebola virus infection. Comparing this response in two different models of exposure (intramuscular and aerosol) revealed a similar signature of infection. The strong innate response in the aerosol model was seen not only in circulating cells, but also in primary and secondary target tissues. Conversely, the innate immune response of vaccinated macaques was almost non-existent. This suggests that the innate response is a major aspect of the cellular response to Ebola virus infection in multiple tissues. Conclusions Ebola virus causes a severe infection in humans that is associated with high mortality. The host immune response to virus infection is thought to be an important aspect leading to severe pathology, but the components of this overactive response are not well characterized. Here, we analyzed how circulating immune cells respond to the virus and found that there is a strong innate response dependent on active virus replication. This finding is in stark contrast to in vitro evidence showing a suppression of innate immune signaling, and it suggests that the strong innate response we observe in infected animals may be an important contributor to pathogenesis.